Introduction to clinical nutrition - Sardesai, Vishwanath M., 1932- (Boca Raton, Fl. : CRC Press, 2012)
'Dietary factors have been implicated in at least four of the ten leading causes of death in the U.S. (heart disease, cancer, diabetes, and stroke). Nevertheless, physicians frequently receive inadequate training in nutrition to properly counsel their patients. Introduction to Clinical Nutrition, Third edition discusses the physiologic and metabolic interrelationships of all nutrients and their roles in health maintenance and the prevention of various diseases.Since the publication of the second edition of this book, new discoveries have revolutionized the field of clinical nutrition. This is true especially with respect to gene-nutrient interaction, epigenetic pathways that contribute to the activation and inactivation of gene expression, the relationship of nutrients to telomere length and health, and personalized nutrition. Highlighting these advances, new and revised topics include: Fiber, antioxidants, nutraceuticals, alternative medicine, and epidemiology DNA, gene nutrient interaction, epigenetics, and telomeres Nutritional aspects of kidney disease, diabetes, and metabolic syndrome personalized nutrition and personalized medicine vegetarianism, the Mediterranean diet, and other popular dietary practices. Obesity and cholesterol. Designed as a textbook for students in conventional medicine, osteopathy, dentistry, dietetics, nursing, pharmacy, and public health, the book focuses on the critical biochemical and physiological aspects of nutrients. It includes clinical case studies to clarify topics at the end of most chapters and references to facilitate further study'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Nutrition